Pendidikan Kesehatan tentang Pemanfaatan Kedelai dan Produk Olahannya sebagai Upaya Mengurangi Ketidaknyaman pada Wanita Perimenopause - Sri Handayani; Irni Setyawati; Yopi Suryatim Pratiwi; Yesvi Zulfiana (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The number of women entering the climacteric phase is expected to increase. Menopausal women will experience a decrease in the amount of estrogen, causing various discomforts. Soybeans and their processed products act as natural estrogens. Objective: to increase perimenopausal women's knowledge about the utilization of soy and its processed products as an effort to reduce discomfort in perimenopausal women. Methods: counseling, discussion, question and answer, and pretest and posttest. Results: there was an increase in the knowledge of perimenopausal women's who had good knowledge of 23,4%, that is, from 66,7% it increased to 90,1%. Conclusion: there is an increase in perimenopausal women's knowledge about the use of soy and its processed products as an effort to reduce discomfort in perimenopausal women. It is recommended for perimenopausal women to increase consumption of soy and its processed products to reduce complaints during perimenopause.